Local structure and optical absorption of Mn2+ doped Cs2SO4 single crystals - Bharati, Maroj; Singh, Vikram; Kripal, Ram (European Journal of Chemistry, 2025)
Using perturbation theory and the superposition model, the splitting parameters for the zero field of Mn2+ doped crystals of Cs2SO4 are determined. When the local distortion is included in the computation, the estimated parameters match fairly well with the experimental ones. Theoretical evidence corroborates the experimental finding that the Mn2+ ion substitutes at the Cs+ site in Cs2SO4. The crystal’s optical spectra are computed by the diagonalization of a complete Hamiltonian in the coupling scheme of the intermediate crystal-field, using the crystal field parameters obtained from the superposition model and the crystal field analysis program. The calculated and experimental band positions agree fairly well. Consequently, the results of the experiment are confirmed by theoretical analysis.